Implementing a student-managed cryptoasset fund in a finance curriculum. Issue 4 (8th February 2022) - Carpenter, Tim
Abstract : Purpose: In 2004, Roanoke College began offering a Student-Managed Fund course, wherein students were able to manage a portfolio of equity and fixed income using real money. While not a widely adopted concept at the time, it has since become quite common in finance programs, either through courses or clubs. In February 2019, the author supplemented activities in the course with the addition of real cryptoassets for students to manage. The paper discusses the design, implementation, and pedagogical advantages of the fund. Design/methodology/approach: The paper expands on the existing literature regarding student-managed investment funds (SMIFs or SMFs) by presenting a case study on the implementation of a student-managed cryptoasset fund at Roanoke College. Findings: The value of experiential learning through student-managed funds (SMFs) is well established. Thus, these programs have become much more common in recent years and are now often expanding to securities beyond equities and bonds. The introduction of cryptoassets to be traded by students at Roanoke College is another step in improving students' exposure to various markets and appears to further improve research and critical thinking skills. Originality/value: This is certainly one of the first, and to the author's knowledge may be the only, real money cryptoasset fund managed by students.